Prevalence of type 2 diabetes and its association with measures of body composition among African residents in the Netherlands – The HELIUS study. Issue 2 (November 2015) - Meeks, Karlijn A.C.; Stronks, Karien; Beune, Erik J.A.J.; Adeyemo, Adebowale; Henneman, Peter; Mannens, Marcel M.A.M.; Nicolaou, Mary; Peters, Ron J.G.; Rotimi, Charles N.; Snijder, Marieke B.; Agyemang, Charles
Highlights: Type 2 diabetes prevalence is higher in African descent populations than Europeans. However, we found important differences between the African descent groups. Ghanaian migrants have higher type 2 diabetes prevalence than African Surinamese. Body composition only accounted partly for ethnic differences in type 2 diabetes. There is a need to distinguish between African descent populations in future research. Abstract: Aims: To compare type 2 diabetes prevalence among three ethnic groups resident in the Netherlands: Ghanaians, African Surinamese and Dutch origin. Secondly, to determine the contribution of measures of body composition to ethnic differences in type 2 diabetes. Methods: Baseline data from Ghanaian ( n = 1873), African Surinamese ( n = 2189) and Dutch ( n = 2151) origin participants of the HELIUS study (aged 18–70 years) were analyzed. Type 2 diabetes was determined according to the WHO criteria. Logistic regression tested ethnic differences in type 2 diabetes and the contribution of body fat percentage and waist-to-hip ratio. Results: Among men, type 2 diabetes prevalence was higher in Ghanaians (14.9%) than in African Surinamese (10.4%) and Dutch (5.0%). Among women, type 2 diabetes prevalence in Ghanaian (11.1%) was higher than in Dutch (2.3%), but similar to African Surinamese (11.5%). After adjusting for age, body fat percentage and waist-to-hip ratio, the odds ratios for having type 2 diabetes were 1.55 (95% CI: 1.12-2.15) for Ghanaian men compared with African Surinamese and 4.19 (95% CI: 2.86-6.12) compared with Dutch. Among women these odds ratios were 0.94 (95% CI: 0.70-1.26) and 4.78 (95% CI: 2.82-8.11). Conclusions: The higher prevalence of type 2 diabetes among Ghanaian compared with African Surinamese men suggests a need to distinguish between African descent populations when assessing their type 2 diabetes risk. The higher odds for type 2 diabetes among Ghanaians cannot be attributed to differences in body composition. Further research on the contribution of lifestyle factors as well as genetic and epigenetic factors is needed to identify the reasons for the observed disparities.